Cyclophosphamide and etoposide therapy with GM‐CSF for VAD‐resistant multiple myeloma - Dimopoulos, M.A.; Delasalle, K.B.; Champlin, R.; Alexanian, R. (British Journal of Haematology, 1993)
Few effective regimens are available for patients with advanced multiple myeloma resistant to or relapsing after both alkylating agents and VAD. We treated 52 patients with advanced and refractory multiple myeloma with the combination of cyclophosphamide (3.0 g/m2) and etoposide (900 mg/m2) followed by GM‐CSF at a daily dose of 0.125 mg/m2 until recovery of granulocytes. 42% of patients responded with a median time of 19 d for recovery of granulocytes to 0.5 x 109/1 and a 4% mortality rate. Eight responding patients received a second myeloablative treatment supported by either autologous bone marrow (six patients) or blood stem cells (two patients). The median survival time for all patients was 11 months and the median remission time for responding patients was 8 months. The combination of cyclophosphamide and etoposide provided an effective rescue treatment for many patients with advanced multiple myeloma resistant to conventional therapies. This programme also allowed early marrow or blood stem cell collection in support of subsequent myeloablative therapy for selected patients. Copyright © 1993, Wiley Blackwell. All rights reserved